Spontaneous Breathing in Early Acute Respiratory Distress Syndrome: Insights From the Large Observational Study to UNderstand the Global Impact of Severe Acute Respiratory FailurE Study*. Issue 2 (February 2019) - van Haren, Frank; Pham, Tài; Brochard, Laurent; Bellani, Giacomo; Laffey, John; Dres, Martin; Fan, Eddy; Goligher, Ewan C.; Heunks, Leo; Lynch, Joan; Wrigge, Hermann; McAuley, Danny
Abstract : Objectives: To describe the characteristics and outcomes of patients with acute respiratory distress syndrome with or without spontaneous breathing and to investigate whether the effects of spontaneous breathing on outcome depend on acute respiratory distress syndrome severity. Design: Planned secondary analysis of a prospective, observational, multicentre cohort study. Setting: International sample of 459 ICUs from 50 countries. Patients: Patients with acute respiratory distress syndrome and at least 2 days of invasive mechanical ventilation and available data for the mode of mechanical ventilation and respiratory rate for the 2 first days. Interventions: Analysis of patients with and without spontaneous breathing, defined by the mode of mechanical ventilation and by actual respiratory rate compared with set respiratory rate during the first 48 hours of mechanical ventilation. Measurements and Main Results: Spontaneous breathing was present in 67% of patients with mild acute respiratory distress syndrome, 58% of patients with moderate acute respiratory distress syndrome, and 46% of patients with severe acute respiratory distress syndrome. Patients with spontaneous breathing were older and had lower acute respiratory distress syndrome severity, Sequential Organ Failure Assessment scores, ICU and hospital mortality, and were less likely to be diagnosed with acute respiratory distress syndrome by clinicians. In adjusted analysis, spontaneous breathing during the first 2 days was not associated with an effect on ICU or hospital mortality (33% vs 37%; odds ratio, 1.18 [0.92–1.51]; p = 0.19 and 37% vs 41%; odds ratio, 1.18 [0.93–1.50]; p = 0.196, respectively ). Spontaneous breathing was associated with increased ventilator-free days (13 [0–22] vs 8 [0–20]; p = 0.014) and shorter duration of ICU stay (11 [6–20] vs 12 [7–22]; p = 0.04). Conclusions: Spontaneous breathing is common in patients with acute respiratory distress syndrome during the first 48 hours of mechanical ventilation. Spontaneous breathing is not associated with worse outcomes and may hasten liberation from the ventilator and from ICU. Although these results support the use of spontaneous breathing in patients with acute respiratory distress syndrome independent of acute respiratory distress syndrome severity, the use of controlled ventilation indicates a bias toward use in patients with higher disease severity. In addition, because the lack of reliable data on inspiratory effort in our study, prospective studies incorporating the magnitude of inspiratory effort and adjusting for all potential severity confounders are required. Abstract : Supplemental Digital Content is available in the text.